Tingkat Pengendalian Emosi Mahasiswa Bimbingan dan Konseling Universitas Sanata Dharma Angkatan 2023 - Alfonsus Tegar Wahyu Budi Kurnia (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
The background of this research is to determine the importance of controlling emotions in supporting students' social relationships. This research aims to (1) Determine the level of emotional control of Guidance and Counseling Students at Sanata Dharma University class of 2023. (2) Identify measurement items on questionnaire items for the level of emotional control of guidance and counseling students at Sanata Dharma University class of 2023 whose scores are low.This research is quantitative descriptive. The subjects of this research were Guidance and Counseling Students at Sanata Dharma University Class of 2023, totaling 47 students. Data collection used the level of emotional control scale with 42 valid items and has a Cronbach index of 0.761 which is based on aspects of emotional control, namely (1) emotional control, (2) assessing situations critically before reacting emotionally, (3) self-understanding.The research results show that (1) the level of emotional control is in the medium category (100%). (2) the emotional control instrument contained 2 item (4,8%) in the very high category, 14 items (33.3%) in the high category, 11 items (26.6%) in the medium category, 11 items (26.6%) %) in the low category, 4 items (9,5%) in the very low category.